CARBON LOSS AFFECTED BY FIRES ON VARIOUS FORESTS AND LAND TYPES IN SOUTH SUMATERA - Siahaan, Hengki; Kunarso, Adi; Sumadi, Agus; Purwanto, Purwanto; Rusolono, Teddy; Tiryana, Tatang; Sumantri, Hendy; Haasler, Berthold (Indonesian Journal of Forestry Research, 2020)
Forest and land fires are a high source of emissions in South Sumatera. In line with the national policy, South Sumatera Province commits in reducing emission, include emission from the forest and land fire. This research was aimed to assess carbon loss affected by fire in the year of 2015 that covered 3 districts in South Sumatera i.e Musi Banyuasin, Banyuasin, and Musi Rawas. The research was conducted by remeasurement of carbon stocks plots on 4 forests and land type i.e. secondary peat swamp forest, secondary dryland forest, bushes swamp, and forest plantation. Carbon stocks measuring are conducted on sample plots in a rectangular shape of 20 m x 50 m of size for various types of natural forest and a circle shape in the radius of 11.29 cm and 7.98 cm respectively for forest plantation of < 4 years and > 4 years old. Furthermore, carbon stocks in each plot are measured for 3 carbon pools of above-ground biomass, deadwood and litter. The result shows that carbon loss was varying on each forest and land type. The largest number of carbon loss occur on secondary peat swamp forest of 94.2 t/ha that equivalent to the emission of 345.4 t CO2eq. The second largest of carbon loss occur on secondary dryland forest of 36.3 t/ha following by forest plantation and bushes swamp of 18.5 t/ha and 13.5 t/ha.